Análisis de las diferentes formas de enlazar teleconsultoríos de centros de salud rurales con hospitales urbanos y elaboración de criterios para seleccionar el método apropiado según el caso - Bucheli, Alfredo (2010)
To accomplish the health services in rural areas, the public or private institutions have found a way on through the development of telecommunications, giving rise to new applications, such is the case of Ttelemedicine. This work has focused on Ecuador, for this reason it has been collected and tabulated information needed to establish data links, which will then be analyzed by the selection criteria and that will allow the consultant to know the proper method to use to establish connection between urban health center and a rural center. As a support tool for the analysis, it was developed a software application that allows visual understanding of the link selection method.